Gandhi in the West : The Mahatma and the Rise of Radical Protest - Scalmer, Sean, 1971- (New York : Cambridge University Press, 2011)
"The non-violent protests of civil rights activists and anti-nuclear campaigners during the 1960s helped to redefine Western politics. But where did they come from? Sean Scalmer uncovers their history in an earlier generation's intense struggles to understand and emulate the activities of Mahatma Gandhi. He shows how Gandhi's non-violent protests were the subject of widespread discussion and debate in the USA and UK for several decades. Though at first misrepresented by Western newspapers, they were patiently described and clarified by a devoted group of cosmopolitan advocates. Small groups of Westerners experimented with Gandhian techniques in virtual anonymity and then, on the cusp of the 1960s, brought these methods to a wider audience. The swelling protests of later years increasingly abandoned the spirit of non-violence, and the central significance of Gandhi and his supporters has therefore been forgotten. This book recovers this tradition, charts its transformation, and ponders its abiding significance"--
Machine generated contents note: Introduction; 1. Meeting the Mahatma; 2. Gandhism in action; 3. At war over words; 4. Waiting for the peace train; 5. The experimenters; 6. An idea whose time has come?; 7. Transformations unforeseen; Conclusion.
Includes bibliographical references and index.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Influence; Nonviolence -- Great Britain -- History -- 20th century; Nonviolence -- United States -- History -- 20th century; Protest movements -- Great Britain -- History -- 20th century; Protest movements -- United States -- History -- 20th century; Antinuclear movement -- Great Britain -- History -- 20th century; African Americans -- Civil rights -- History -- 20th century; Civil rights movements -- United States -- History -- 20th century; HISTORY / Modern / 20th Century